(untitled) (International journal of artificial intelligence, 2025)
This article presents the current conceptual methods for analyzing the composition of substances, along with their analysis methods Izertlev's research investigated the accuracy and convenience of research using the Ozhe spectroscopy method for scientific and laboratory activities. Actually atomic spectroscopy is widely used for green chemistry.